Assessing tackle performance using a novel collision sport simulator in comparison to a "live" one-on-one tackling drill. Issue 1 (2nd January 2019) - Burger, Nicholas; Lambert, Michael Ian; Hall, Harry; Hendricks, Sharief
ABSTRACT: It is necessary to study the rugby tackle as it is associated with successful performance outcomes and is responsible for the majority of contact injuries. A novel collision sport simulator was developed to study tackle performance. The main aim of this validation study was to assess tackle technique performance between two different conditions: simulator versus a standardised one-on-one tackle drill previously used to assess technique. Tackling proficiency was assessed using a list of technical criteria. Mean scores, standard deviations and Cohen's d effect sizes were calculated. Mean overall score for dynamic i.e. running simulator tackles was 7.78 (95%CI 7.58–7.99) (out of 9) or 87% (standard deviation or SD±8.94), and mean overall score for dynamic "live" tackles was 7.85 (95%CI 7.57–8.13) (out of 9) or 87% (SD±9.60) (effect size = 0.08; trivial; p > 0.05). Mean overall score for static i.e. standing simulator tackles was 7.45 (95%CI 7.20–7.69) (out of 9) or 83% (SD±10.71), and mean overall score for static "live" tackles was 8.05 (95%CI 7.83–8.27) (out of 9) or 89% (SD±7.53) (effect size = 0.72; moderate; p < 0.001). The simulator replicates dynamic tackle technique comparable to real-life tackle drills. It may be used for research analysing various aspects of the tackle in rugby and other contact sports.